Thermoelectric Characterization of IGBT Power Modules: An Approach by Static and Dynamic Methods - Deivid F. de Souza; Diego S. Greff (Eletrônica de Potência)
This study evaluates IGBT modules with a focus on efficiently measuring their thermal impedance, a critical factor in reliability assessments. The research employs the Thermo Electric Sensitive Parameter method to measure the Virtual Junction Temperature and obtain the Thermal Impedance curve. These experimental results are compared with datasheet values, using power modules without a baseplate. Two methodologies, dynamic and static, are utilized, both demonstrating consistent performance in evaluating thermal characteristics. The study also addresses the importance of accounting for non-linearity in thermal conductance due to temperature dependency, which is essential for accurate thermal characterization. Additionally, it explores the potential for measuring the Thermal Impedance between Junction and Case in power modules without a baseplate, offering a comprehensive understanding of thermal performance.